2014
DOI: 10.1002/hyp.10264
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hydropeaking on hyporheic interactions based on field experiments

Abstract: 36Hydropeaking power production has the potential to pose serious challenges towards and positions in the river bed that can be potentially relevant to ecology were investigated. 47Understanding the complexity of those processes at the fine scale from the physical point of 48 view is both important for the judgment of potential ecological impacts and for the future 49 management of such regulated systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Similarly to the high flow, ice-induced low flows are mainly estimated by comparing the raw and corrected data, and, in cases where there are no available air temperature changes in the gradient of the recession, hydrograph is used to detect drops in the flow caused by ice. For small streams, the rate of change of the water level related to such low flows can be significant, and the maximum rate of change is computed following similar procedures, as for hydropeaking analysis [31].…”
Section: Analysis and Extended Indicesmentioning
confidence: 99%
“…Similarly to the high flow, ice-induced low flows are mainly estimated by comparing the raw and corrected data, and, in cases where there are no available air temperature changes in the gradient of the recession, hydrograph is used to detect drops in the flow caused by ice. For small streams, the rate of change of the water level related to such low flows can be significant, and the maximum rate of change is computed following similar procedures, as for hydropeaking analysis [31].…”
Section: Analysis and Extended Indicesmentioning
confidence: 99%
“…Even though this is not a direct equivalent of the porous structure in a real gravel bed, the number of holes can still be associated with a measurable porosity of the streambed. Each hole has a diameter of 3 mm, giving it a surface area of Ahole = 7.07 mm 2 . The total size of the modified area is = (400 mm) 2 = 160,000 mm 2 .…”
Section: Influence Of the Armor Layer Porositymentioning
confidence: 99%
“…As a practical example: Recent field studies on hydropower peaking have shown that unsteadiness parameters of = 0.0180 and higher, also occur in real gravel bed streams. Applying Equation (2) to the raw data of a field study at River Lundesokna in Norway [2], a hydrograph with an unsteadiness parameter of = 0.0183 could be observed downstream a hydropower plant on 30 January 2012. In comparison, the largest unsteadiness parameter in the study of [3] is = 0.0180, resulting in hardly recognizable significant unsteady effects for this measurement range (Figure 7).…”
Section: Range Of Unsteadiness Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date, only few attempts have been made to relate flow regulation to river temperature in order to define management practices able to protect both aspects of fluvial environment . For the definition of adequate remediation actions, the effects of river discharge alteration on water temperature should be detected at different temporal (Hari et al, 2006;Toffolon et al, 2010;Zolezzi et al, 2011;Vanzo et al, 2016) and spatial scales Gerecht et al, 2011;Casas-Mulet et al, 2015). Recent studies (Toffolon et al, 2010;Zolezzi et al, 2011;Carolli et al, 2012;Bruno et al, 2013;Vanzo et al, 2016) focused on the identification of the relationships between hydropeaking and thermopeaking, and their ecological effects, mainly on short and medium timescales and in a mountainous context.…”
Section: Introductionmentioning
confidence: 99%